Case report: Sex-specific characteristics of epilepsy phenotypes associated with Xp22.31 deletion: a case report and review - Yi Wu; Dan Wu; Dan Wu; Yulong Lan; Yulong Lan; Shaocong Lan; Duo Li; Zexin Zheng; Hongwu Wang; Lian Ma; Lian Ma; Lian Ma; et al. (Frontiers in Genetics, 2023)
Deletion in the Xp22.31 region is increasingly suggested to be involved in the etiology of epilepsy. Little is known regarding the genomic and clinical delineations of X-linked epilepsy in the Chinese population or the sex-stratified difference in epilepsy characteristics associated with deletions in the Xp22.31 region. In this study, we reported two siblings with a 1.69 Mb maternally inherited microdeletion at Xp22.31 involving the genes VCX3A, HDHD1, STS, VCX, VCX2, and PNPLA4 presenting with easily controlled focal epilepsy and language delay with mild ichthyosis in a Chinese family with a traceable 4-generation history of skin ichthyosis. Both brain magnetic resonance imaging results were normal, while EEG revealed epileptic abnormalities. We further performed an exhaustive literature search, documenting 25 patients with epilepsy with gene defects in Xp22.31, and summarized the epilepsy heterogeneities between sexes. Males harboring the Xp22.31 deletion mainly manifested with child-onset, easily controlled focal epilepsy accompanied by X-linked ichthyosis; the deletions were mostly X-linked recessive, with copy number variants (CNVs) in the classic region of deletion (863.38 kb–2 Mb). In contrast, epilepsy in females tended to be earlier-onset, and relatively refractory, with pathogenic CNV sizes varying over a larger range (859 kb–56.36 Mb); the alterations were infrequently inherited and almost combined with additional CNVs. A candidate region encompassing STS, HDHD1, and MIR4767 was the likely pathogenic epilepsy-associated region. This study filled in the knowledge gap regarding the genomic and clinical delineations of X-linked recessive epilepsy in the Chinese population and extends the understanding of the sex-specific characteristics of Xp22.31 deletion in regard to epilepsy.